Numerical Investigation on the Performance of Suction Head in a Cleaning Process of Hard Disk Drive Factory - Jirawat Khongsin; Jatuporn Thongsri (My University, 2020)
The suction head is a component positioned at the vacuum cleaner’s tip and used to control airflow to eliminate small particles, thus preventing contamination from occurring during the cleaning process at a hard disk drive (HDD) manufacturing factory. At the factory, 2 suction head types (bowl and straight) were used in the cleaning process. From actual usage, the operators questioned the operating condition’s performance and suitability. In order to seek an answer to the questions, the researchers used computational fluid dynamics (CFD) to simulate airflow and particle trace using the FLUENT program, the factory’s actual conditions, and a suction distance ranging between 2.5-15 mm. CFD simulation results showed that the bowl type suction head performed better compared to the straight type in every suction range under the exact same operating conditions. Both suction heads performed well at a 5 mm distance between the suction head and cleaning area. Suction performance decreased when the head was positioned closer or farther than the mentioned distance. Apart from applying all results from this research to increase cleaning efficiency in the actual factory, the findings could also be used as basic information for designing new suction head models with higher efficiency than the original model.
Keywords: Factory (object-oriented programming); Particle Dynamics in Fluid Flows